Human Resource Corporation (HRD Corp) / Nur Zarif Sofea Mohd Samsuri - Mohd Samsuri, Nur Zarif Sofea (Faculty of Business and Management, 2023)
Starting on May 1st, 2023, I began my internship at Human Resource Corporation (HRD Corp) headquarters in Damansara Heights, Kuala Lumpur. The purpose of this internship w as to fulfill the requirements of m y final year degree in Business Administration with a specialization in Finance from Universiti Teknologi Mara Campus Bandaraya Melaka. The internship lasted for six months, concluding on August 15th, 2023. HRD Corp's standing as a prominent Government-Linked Company under the Ministry of Human Resource which responsible to provide training funded through levy collection. My aim w as to gain exposure to the company's operations and processes, particularly in understanding how HRD Corp m an ag e san d implements its training initiatives. During m y internship, I was assigned to the Risk, Management, and Compliance Department, w here I had the responsibility of engaging with two distinct work scopes: Risk and Compliance. Despite it not being m y initial area of interest, this new experience unlocked met to expand m y knowledge and effectively apply my Business Administration skills in a fresh context. Throughout m y internship, I realized the importance of risk identification in a company. I successfully completed a Risk Assessment Session within two months, which had a significant impact on the company performance. I gained valuable experience in preparing Quality Management Systems, developing Standard Operating Procedures, and participating in internal audit planning. Overall, m y internship at HRD Corporation provided me with practical experience and valuable insights into the Risk Management and Compliance Department. Through completing various tasks, I not only developed technical skills but also improved my communication and problem -solving abilities. I believe that the findings and recommendations presented in this report can contribute to the continuous improvement and growth of HRD Corporation.